1998
DOI: 10.1002/(sici)1096-9845(199810)27:10<1013::aid-eqe765>3.0.co;2-0
|View full text |Cite
|
Sign up to set email alerts
|

Modelling of contraction joint and shear sliding effects on earthquake response of arch dams

Abstract: In an arch dam, adjacent monoliths separated by vertical contraction joints may move relative to each other during an earthquake, resulting in the gradual opening and closing and possible shear movement at the joint surfaces. This paper presents the formulation of a joint constitutive model for a zero-thickness joint element that can simulate both the opening and closing and shear sliding behaviour, as well as the non-linear shear key e ects of the joint. The proposed joint element has been implemented in the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
26
0

Year Published

2004
2004
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 54 publications
(26 citation statements)
references
References 10 publications
0
26
0
Order By: Relevance
“…Each natural frequency must satisfy the characteristic polynomial defined in Eq. (6). By substituting the j th natural frequency, i.e.…”
Section: Joint Identification Approachmentioning
confidence: 99%
See 1 more Smart Citation
“…Each natural frequency must satisfy the characteristic polynomial defined in Eq. (6). By substituting the j th natural frequency, i.e.…”
Section: Joint Identification Approachmentioning
confidence: 99%
“…Without considering a thickness for contact interface, in zero thickness elements, a constitutive relation with constant stiffness values for normal and tangential directions is considered [5]. In thin layer elements the contact interface is modeled with finite thickness elements similar in formulation to the brick element [6]. The lumped spring and the generic joint models being usually used to model contact interfaces can be respectively categorized as zero thickness and thin layer interface elements.…”
Section: Introductionmentioning
confidence: 99%
“…Several researchers [3,8,23] have studied the effect of contraction joints on the seismic response of arch dams. In their models, the joins were modeled by the joint-element.…”
Section: Modeling Of Nonlinear Contraction Jointmentioning
confidence: 99%
“…In recent years, considerable research efforts have been devoted to seismic safety study of arch dams. Some major influential factors, including dynamic dam-water-foundation interaction [1][2][3], non-uniform seismic input [4][5][6], contraction joint opening and closing [7,8], damage evolution [9,10], contraction joint reinforcement [11], reservoir sediment [12], etc., have been considered in the safety assessment of arch dams against earthquakes. One unknown factor that may have effects on the seismic safety of dams is the aging of concrete dams.…”
Section: Introductionmentioning
confidence: 99%
“…But in this model, the convergence of the numerical results is difficult to be ensured and the parameters are also difficult to be chosen. A complete joint constitutive model that could both simulate opening-closing and shear slippage nonlinear effects, as well as the shear key effects had been formulated and implemented into program ADAP-88 by Lau et al [15]. Results of their studies showed that shear slippage across the contraction joints could cause very important changes in the displacement and stress fields of an arch dam.…”
Section: Introductionmentioning
confidence: 99%